Women and Civil Society: Capacity Building in Yemen - Maggy Grabundzija, Blandine Destremau (Centre français de recherche de la péninsule Arabique, 2011)
This work is the result of fruitful collaboration between the department of cooperation in the French Embassy in Sana'a and CEFAS (French CEnter for Archeology and Social Sciences in Sanna). It aims to present a joint reflection on experiences in gender and development projects, and to join in the debate they foster not only in Yemen, but on a much wider scale as well, beyond cultural and contextual particularities. This initiative connects with practical and critical research concerned with ...